Pengaruh Perceived Value Terhadap Purchase Intention Digital Music Streaming Services Dengan Satisfaction Sebagai Variabel Intervening (Studi Pada Aplikasi Joox dan Spotify) - Aruna Candra Pratiwi; Bambang Munas Dwiyanto (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2021)
This study aims to analyze the effect of perceived value on the satisfaction of digital music streaming services Joox and Spotify applications and their effects on consumer purchase intentions. The variables used in this study are perceived value as an independent variable, then satisfaction as an intervening variable, and purchase intention of paid applications as the dependent variable. The number of samples in this study amounted to 133 respondents, namely users of digital music streaming services, especially the Joox and Spotify applications. The method used is non-probability sampling by distributing questionnaires to respondents. In this study, a theoretical model was developed by proposing five hypotheses to be tested using Structural Equation Modeling (SEM) analysis tools operated through the AMOS 24 program. The results of this study indicate that perceived value increases user satisfaction, which affects the purchase intention of paid applications.